The Cambridge Shakespeare guide - Smith, Emma (Cambridge University Press India Pvt. Ltd., 2012)
"Are you studying Shakespeare and looking for a handy summary of plots, characters and interpretations? Or are you a keen theatregoer wanting essential background on the Shakespeare plays you see on stage? Ideal for students and theatre enthusiasts alike, this lively and authoritative guide presents key information, clearly set out, on all Shakespeare's dramatic and poetic works, covering plots and people, sources, context, performance history and major themes. Ordered alphabetically for easy reference, each play entry features a 'key facts' box providing informative and revealing statistics, including a breakdown of each play's major roles. The guide is illustrated with striking performance photographs throughout, and also provides brief accounts of Shakespeare's life and language, Shakespeare in print and theatre in Shakespeare's time. This is an indispensable reference source for all students and theatregoers"--